Pengaruh Pengangguran, Pembangunan Manusia, dan Upah Minimum Terhadap Kemiskinan di Provinsi Papua - Jati, Damar; Purnomo, Sodik Dwi; Retnowati, Diah; Zumaeroh, Zumaeroh (SJEE (Scientific Journals of Economic Education), 2024)
Poverty is a major concern for governments around the world, especially in developing countries such as Indonesia. In Indonesia, the government prioritizes poverty alleviation as part of efforts to improve people's welfare. This study aims to examine the influence of unemployment, human development index, and regional minimum wage on poverty in districts/cities in Papua Province during the period 2017-2021. Data from 29 districts/cities in Papua were analyzed using the panel data regression method. The three estimation approaches used include common effect, fixed effect, and random effect. Based on the results of the best model selection test, random effect was selected as the most suitable model. The analysis using this model shows that unemployment has a negative impact on poverty, contrary to the hypothesis that unemployment has a positive impact. In addition, the human development index also has a negative influence on poverty, while the regional minimum wage has no significant effect on poverty levels.